2006
DOI: 10.1016/j.otohns.2006.05.750
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of frontal pneumatization patterns between Koreans and Caucasians

Abstract: Frontal recess pneumatization patterns differ in the Korean and Caucasian adult populations. Because corresponding differences in skull base length were not identified, these differences seem likely to reflect other factors. Such information has clinical significance for frontal recess surgery in these patient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
56
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 11 publications
10
56
4
Order By: Relevance
“…Anatomically, it is the most anterior ethmoid cell pneumatizing laterally into the lacrimal bone. Our data indicate that the prevalence of the agger nasi cell may be as high as 93.9%, in line with studies conducted by other investigators [14][15][16]20] (from 86.7% [15] to nearly 100% [20] ). By using the agger nasi cell as an anatomical landmark (the agger nasi cell approach) [18] , the endoscopic frontal recess operation starts with opening of the anteroinferior wall of the agger nasi cell followed by removal of the medial, roof and posterior walls of the agger nasi cell.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Anatomically, it is the most anterior ethmoid cell pneumatizing laterally into the lacrimal bone. Our data indicate that the prevalence of the agger nasi cell may be as high as 93.9%, in line with studies conducted by other investigators [14][15][16]20] (from 86.7% [15] to nearly 100% [20] ). By using the agger nasi cell as an anatomical landmark (the agger nasi cell approach) [18] , the endoscopic frontal recess operation starts with opening of the anteroinferior wall of the agger nasi cell followed by removal of the medial, roof and posterior walls of the agger nasi cell.…”
Section: Discussionsupporting
confidence: 93%
“…2 a, c), the frontal recess could be reached anteriorly or inferiorly without obstructing cells above it by using different approaches [18,22] . Although Lee et al [14] reported that the prevalence of frontal cells was as high as 64%, 3 others found lower rates (25.5% [15] , 20.4% [13] and 44.7% in Koreans [16] ); our findings (39.6%) are generally in line with the latter 3 reports. Complex situations arose when the frontal cells had anterior blockages in the frontal sinus drainage pathway.…”
Section: Discussionsupporting
confidence: 89%
“…Bent III et al 10 in their study correlated the presence of frontal cells in CT scan and intraoperatively -they found the incidence of type III or IV frontal cells to be between 1 and 2%. Cho et al 11 found frontal cell type I in 22.8%, type II in 14%, type III in 7.9%, and type IV in 0% in CT scan. The CT showed positive correlation with intraoperative findings (coefficient of correlation 0.88) in identification of frontal bullar cells.…”
Section: Discussionmentioning
confidence: 96%
“…These cells drain into the one of the FR and are well defined in the coronal and axial scans [57]. The incidence rate in the literature is reported as 12.4 [56] and 14% [58].…”
Section: Interfrontal Sinus Septa Cellmentioning
confidence: 94%
“…On coronal images, the presence of bony septum between the ethmoid complex and the recess separates the frontal sinus from the SOEC [18]. These cells drain into the lateral aspect of the FR [57]. Because of the close relation between the SOEC and anterior ethmoidal artery, enlarging the SOEC could risk damage to the artery [59].…”
Section: Supraorbital Ethmoid Cellmentioning
confidence: 99%